"Rough Week for Testosterone": Public Commentary around the Ivy League's Decision to Restrict Tackle Football in Practice. Issue 5 (20th October 2018) - Cranmer, Gregory A.; Sanderson, Jimmy
Abstract : This research examines public dialogue about the decision of the Ivy League schools to restrict full-contact tackling during football practice. Data from Twitter and online news comments were subjected to interpretive analysis, which revealed that participants framed the policy as evidence of social progress while others critiqued its effectiveness and positioned it as evidence of the decline of masculinity and American identity. The results indicate that public discourse around health and safety issues within sport are more complex and varied than those in the media. Additionally, sport organizations should anticipate resistance to policies and strategically craft communication to address these barriers.